Sharpening of the explicit lower bounds for the order of elements in finite field extensions based on cyclotomic polynomials - Popovych, R. (Український математичний журнал, 2014)
We explicitly construct elements of high multiplicative order in any extensions of finite fields based on cyclotomic polynomials.